Onshore and offshore wind energy : an introduction - Lynn, Paul A. (Chichester, West Sussex ; Hoboken, NJ : Wiley, 2012)
"This book uses academic content and rigor to introduce all relevant topics, from global wind resource and historical background, through to modern electricity generation and distribution, including the topical subject area of offshore systems"--
0
Includes bibliographical references and index.
Keywords: Wind power; Offshore electric power plants; Wind energy conversion systems